A conceptual framework on determinants of the integrated tuberculosis control model implementation in China - Chen, Xi; Zhou, Jiani; Yuan, Quan; Huang, Chunji; Li, Ying (Frontiers in Medicine, 2024)
Improving the provision of tuberculosis (TB) care is both urgent and imperative to achieve the goals outlined in the End TB Strategy. China has initiated the integrated TB control model to enhance the quality of TB care Since 2012. Despite these efforts, the integrated TB control health system encounters numerous challenges in delivering effective TB care. The factors influencing TB care provision are intricate, and a conceptual framework to comprehend these potential determinants is currently lacking. To bridge this gap, this article proposed a conceptual framework that was developed through insights from the fields of both public management and health services, adjustment of PRISM model and elements, reference to the blocks of health system and reference to the framework of outcome indicators in implementation research. This conceptual framework included 4 modules which can be coherently and logically deduced, offered a multi-perspective understanding of the determinants to TB care, and hypothesized that the TB control services provided by the integrated TB control model is a public service and must be “patient-centered”; determinants of the integrated TB control model implementation can be divided into seven domains; the evaluation of the integrated TB control model implementation covers implementation outcomes and service outcomes. This framework offers the potential to guide empirical investigations, aiding in the understanding and identification of determinants, including barriers and facilitators, associated with the implementation of the integrated TB control health model. Furthermore, it serves as a valuable tool for developing interventions that address system-level barriers, drawing insights from the realms of public management and health services.